The deprivation of certitude, legitimacy and hope: Foreign national prisoners and the pains of imprisonment. (July 2016) - Warr, Jason
At the end of March 2015 there were 10, 481 foreign nationals (defined as non-UK passport holders) held in prisons in England and Wales, representing 12 per cent of the overall prison population. The latest published figures from December 2014 also indicated that there were a further 394 immigration detainees also being held in various prisons, rather than Immigration Removal Centres, across England and Wales. Although Sykes's deprivation model with its associated 'pains of imprisonment' has been exhaustively explored by penologists, this article argues that there are a new range of 'pains' uniquely faced by foreign national prisoners in England and Wales who come under the scrutiny of the Home Office's Immigration Service. Drawing on quasi-ethnographic fieldwork in a Specialist Foreign National Prison, this article discusses the new pains relating to a lack of certitude, legitimacy and hope with regard to both their carceral and post-carceral lives.